Highly heat-conductive wear-resistant lubricating oil and preparation method thereof
Patent Information
- Application Number
- CN202611401847.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]在润滑油中引入具有层间滑移特性与导热性能的二维纳米材料(如纳米二硫化钼)是改善上述性能的途径之一;然而,纳米颗粒较高的表面能使其在非极性或弱极性基础油中易发生团聚与沉降,不利于维持稳定的热传导网络;尽管常规的表面修饰能在一定程度上改善其分散性,但在高温、高剪切工况下,若改性分子仅依赖物理吸附或较弱的相互作用结合,其脱附风险相对增加;此外,采用大分子改性剂时常受限于空间位阻效应,导致实际接枝率受限,影响了表面修饰的致密性与稳定性
[0023]与现有技术相比,本申请的有益效果至少在于:
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of lubricating oil technology, specifically to a high thermal conductivity and wear-resistant lubricating oil and its preparation method. Background Technology
[0002] As mechanical equipment such as wind turbine gearboxes and industrial robot reducers develop towards higher power, heavier loads, and greater integration, friction pairs are prone to localized heat accumulation (i.e., interface flash temperature) under complex alternating stress and high shear conditions. The long-term coupling of thermal stress and mechanical stress not only increases the risk of adhesive wear and fatigue spalling on metal surfaces, but also accelerates the thermal oxidative degradation of lubricating oil. Therefore, higher comprehensive requirements are placed on the thermal conductivity and heat dissipation capacity, extreme pressure anti-wear properties, and oxidation resistance of lubricating oil.
[0003] Introducing two-dimensional nanomaterials (such as nano-molybdenum disulfide) with interlayer slip properties and thermal conductivity into lubricating oil is one way to improve the aforementioned properties. However, the high surface energy of nanoparticles makes them prone to agglomeration and sedimentation in non-polar or weakly polar base oils, which is not conducive to maintaining a stable heat conduction network. Although conventional surface modification can improve its dispersibility to some extent, under high temperature and high shear conditions, if the modified molecules rely only on physical adsorption or weak interaction binding, the risk of desorption increases relatively. In addition, the use of macromolecular modifiers is often limited by steric hindrance, resulting in a limited actual grafting rate, which affects the compactness and stability of the surface modification.
[0004] On the other hand, to delay oxidative degradation, lubricating oil systems are often compounded with hindered phenols and other small-molecule antioxidants. However, under high temperature and alternating heat and oxygen conditions, the volatility and thermal migration tendency of small-molecule antioxidants increase, limiting their long-term effectiveness. More complicatedly, lubrication systems in service often face the risk of coupled degradation due to friction and oxidation. When antioxidant consumption leads to a decrease in the system's antioxidant capacity, acidic oxidation byproducts can not only easily cause metal corrosion, but may also promote the oxidative degradation of organic modified segments on the surface of nanoparticles, thereby destroying the dispersion system and thermal conductivity network. At the same time, the newly formed active metal surfaces exposed by nanoparticle aggregation or boundary lubrication film damage can easily catalyze the oxidation chain reaction of base oil, accelerating the decline in oil performance.
[0005] In summary, existing lubrication technologies still have certain limitations in balancing the long-term dispersion stability of nano-thermal conductive materials, the high-temperature volatility resistance of antioxidants, and mitigating the coupled degradation of "friction-oxidation".
[0006] Therefore, there is an urgent need to provide a high thermal conductivity and wear-resistant lubricant and its preparation method that can synergistically improve thermal conductivity, extreme pressure anti-wear properties and oxidation resistance, and has good physicochemical stability. Summary of the Invention
[0007] To address the aforementioned issues, this application provides a high thermal conductivity and wear-resistant lubricating oil and its preparation method, achieving excellent thermal conductivity and wear resistance.
[0008] In a first aspect, this application provides a high thermal conductivity and wear-resistant lubricating oil, comprising the following raw materials in parts by weight: 65 parts polyalphaolefin, 12-18 parts pentaerythritol fatty acid ester, 1.5-2.5 parts modified nano molybdenum disulfide, 2-5 parts bio-based macromolecular hindered phenol, 1-3 parts sulfurized isobutylene, 1-3 parts antioxidant, 0.01-0.05 parts defoamer, and 0.01-0.05 parts demulsifier; The modified nano-molybdenum disulfide is a nano-molybdenum disulfide whose surface is reduced with sodium borohydride to introduce sulfur vacancy defects and grafted with long-chain aliphatic amide fragments through Mo-S coordination covalent bonds. The bio-based macromolecular hindered phenol is a graft product obtained by an epoxidized soybean oil and a hindered phenol derivative with a terminal hydrogen active group undergoing an epoxidative ring-opening addition reaction; the hindered phenol derivative with a terminal hydrogen active group includes at least one of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionylhydrazide, and 4-amino-2,6-di-tert-butylphenol.
[0009] This application provides a high thermal conductivity and wear-resistant lubricating oil that addresses the comprehensive performance requirements of equipment such as wind turbine gearboxes and industrial robot reducers for lubricating oil thermal conductivity, extreme pressure wear resistance, and oxidation resistance. By optimizing the base oil system and introducing modified nano-molybdenum disulfide and bio-based macromolecular hindered phenol, a synergistic lubrication system is constructed. Specifically, regarding thermal conductivity and wear resistance, this application introduces sulfur vacancies on the surface of nano-molybdenum disulfide and grafts long-chain aliphatic amides via Mo-S bonds. Utilizing the steric hindrance effect of the grafted segments, the dispersion and suspension stability of this modified nano-molybdenum disulfide in base oil composed of polyalphaolefins and pentaerythritol fatty acid esters are improved, reducing the tendency for agglomeration and sedimentation. This dispersed structure helps form a thermal conductivity network in the base oil, improving the overall thermal conductivity of the resulting high thermal conductivity and wear-resistant lubricating oil. Simultaneously, the modified nano-molybdenum disulfide, combined with sulfurized isobutylene, produces a synergistic effect in the friction contact area, enhancing oil film bearing capacity and initial micro-protrusion... During the contact phase, dispersed nano-molybdenum disulfide preferentially adsorbs and enters the surface micro-pits to physically fill them, providing basic friction reduction based on interlayer slip characteristics. When the contact stress increases dramatically, causing local rupture of the oil film, direct collision of micro-protrusions and induction of interfacial flash temperature, the physical film load-bearing capacity is limited. Isobutylene sulfide is then thermally activated and releases active sulfur, which undergoes a tribochemical reaction with the metal substrate to generate an inorganic sulfide reaction film to prevent adhesion and sintering. The two respond sequentially under different contact stress and interfacial temperature gradients, promoting the formation of a boundary lubrication film on the friction pair surface that combines physical deposition and chemical reaction, thereby improving the overall load-bearing and anti-wear friction-reducing performance. In terms of high-temperature antioxidant properties, this application utilizes epoxidized soybean oil to undergo a ring-opening addition reaction with hindered phenol derivatives containing hydrogen-terminated active groups to prepare bio-based macromolecular hindered phenols. Compared to traditional small-molecule antioxidants, these bio-based macromolecular hindered phenols restrict molecular thermal migration due to their relative molecular mass and spatial volume, reducing the volatilization loss rate under high-temperature conditions. Simultaneously, the inherent long-chain aliphatic hydrocarbon and ester group structures in the soybean oil skeleton match the polarity characteristics of the base oil, improving the compatibility and solubility uniformity of antioxidant molecules in the base oil medium. Under alternating thermo-oxidative conditions, these bio-based macromolecular hindered phenols can be stably retained in high thermal conductivity and wear-resistant lubricating oils and synergistically enhance the oxidation induction period and thermo-oxidative stability of high thermal conductivity and wear-resistant lubricating oils with other antioxidants in the system. Furthermore, the modified nano-molybdenum disulfide and bio-based macromolecular hindered phenols form a synergistic effect based on the friction-oxidation coupling mechanism in the system. On the one hand, the boundary lubrication film constructed by the modified nano-molybdenum disulfide plays a physical isolation role on the metal friction contact surface, reducing the direct contact of metal micro-protrusions and the probability of exposure of the nascent metal surface, and alleviating the associated interface flash temperature. This physically weakens the catalytic initiation of the oxidation chain reaction of the base oil system by the metal substrate, thereby reducing the consumption rate of bio-based macromolecular hindered phenols. On the other hand, the bio-based macromolecular hindered phenols relatively stably quench peroxide free radicals induced by high shear and thermal stress at the base oil medium and friction interface, reducing the generation of acidic oxidation byproducts. This process not only alleviates the corrosion and wear tendency of the metal surface, but also protects the long-chain aliphatic amide graft segments on the surface of the modified nano-molybdenum disulfide from deep oxidative degradation, maintaining its steric hindrance effect, which in turn helps to maintain the suspension stability of the modified nano-molybdenum disulfide in the system under thermo-oxidative aging conditions and maintain the integrity of the thermal network. In terms of base oil system construction and comprehensive physicochemical property control, this application combines non-polar polyalphaolefin with pentaerythritol fatty acid esters containing polyester groups to form a base oil system. Polyalphaolefin provides viscosity retention and thermal oxidation stability over a wide temperature range. Pentaerythritol esters, with their polar structure, not only improve the thermodynamic compatibility and dispersion uniformity of polar additives in the non-polar polyalphaolefin substrate, but their polar groups also exhibit preferential affinity for metal lattices, forming an initial polar adsorbed oil film on the metal surface to provide pre-protection. Furthermore, the formulation includes defoamers and demulsifiers. Defoamers accelerate the collapse of trapped air bubbles under high shear agitation by altering the gas-liquid interfacial tension, maintaining the continuity and incompressibility of the lubricating oil film in the load-bearing area. Demulsifiers, when faced with water intrusion, competitively adsorb and destroy the stable emulsion layer of free water, promoting oil-water separation, thereby reducing the risk of emulsification and deterioration of high thermal conductivity and wear-resistant lubricating oil and improving stability.
[0010] In some embodiments, the modified nano-molybdenum disulfide is prepared by the following steps: M1: Disperse nano-molybdenum disulfide and sodium borohydride in water to remove some sulfur atoms from the surface of nano-molybdenum disulfide to form sulfur vacancies, thereby obtaining defective nano-molybdenum disulfide. Then, disperse the defective nano-molybdenum disulfide and a coordinating fatty acid with active sulfur at the end group in a first organic solvent to form a Mo-S coordination covalent bond with the defective nano-molybdenum disulfide, thereby obtaining carboxylated nano-molybdenum disulfide. M2: The carboxylated nano-molybdenum disulfide, condensing agent, auxiliary condensing agent, and long-chain aliphatic primary amine are dispersed in a second organic solvent, so that the carboxylated nano-molybdenum disulfide reacts with the long-chain aliphatic primary amine to obtain modified nano-molybdenum disulfide.
[0011] Furthermore, the coordinated fatty acid with active sulfur at the end group includes at least one of α-lipoic acid and asparagus acid; The long-chain aliphatic primary amine includes at least one of oleylamine and mustyl primary amine; The condensing agent includes N , N' At least one of dicyclohexylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; The auxiliary condensing agent includes at least one of 4-dimethylaminopyridine, 1-hydroxybenzotriazole, and N-hydroxysuccinimide; The first organic solvent includes at least one of dichloromethane, toluene, and 1,4-dioxane; The second organic solvent includes at least one of dichloromethane, toluene, and 1,4-dioxane.
[0012] Furthermore, the modified nano-molybdenum disulfide is prepared through the following steps: M1: Disperse 10 parts of nano-molybdenum disulfide in 150-250 parts of water, add 1 part of sodium borohydride, and react at 20-30°C for 1-3 hours to obtain defective nano-molybdenum disulfide. Then disperse the defective nano-molybdenum disulfide and 1.8-2.2 parts of coordinated fatty acids with active sulfur end groups in 180-240 parts of a first organic solvent, and react at 20-30°C for 3-4 hours to obtain carboxylated nano-molybdenum disulfide. M2: The carboxylated nano-molybdenum disulfide is dispersed in 180-240 parts of a second organic solvent, and then 1.1-1.5 parts of a condensing agent and 0.05-0.15 parts of an auxiliary condensing agent are added. The mixture is reacted at 0-5°C for 0.5-1 h, and then 1.5-2.5 parts of a long-chain aliphatic primary amine are added. The mixture is reacted at 20-30°C for 8-12 h to obtain modified nano-molybdenum disulfide.
[0013] Furthermore, the nano-molybdenum disulfide is in the form of flakes, 2H phase, with an average particle size of 75–125 nm, an aspect ratio of 10–50:1, and a specific surface area of 40–80 m². 2 / g.
[0014] Through the above implementation method, sheet-like nano-molybdenum disulfide is used as the matrix. Its layered structure provides interlayer slip characteristics to assist in friction reduction. The two-dimensional extensibility and specific surface area of the sheet-like structure provide reaction sites for subsequent surface chemical modification and facilitate their interlocking in the base oil system, providing a structural basis for constructing a heat-conducting network. In step M1, sodium borohydride is used to partially desulfurize nano-molybdenum disulfide to form sulfur vacancies, exposing coordinated unsaturated molybdenum sites. A coordination fatty acid with active sulfur end groups is introduced, and its active sulfur end groups coordinate with the sulfur vacancies to form Mo-S coordination covalent bonds. Compared with physical adsorption, this chemical coordination mechanism anchors the carboxyl-containing molecular chains more stably to the matrix surface, reducing their desorption and loss under stress and heat conditions. Step M2 utilizes a condensation system to induce an amidation reaction between the carboxyl groups on the surface of carboxylated molybdenum disulfide nanoparticles and long-chain aliphatic primary amines, grafting long-chain aliphatic amide fragments. This long-chain structure matches the polarity and molecular configuration of the base oil, improving the wettability of the nanoparticles in the organic oil phase. At the same time, the steric hindrance effect of the surface grafted segments weakens the interaction between particles and reduces the tendency for agglomeration and sedimentation. After the above modifications, the dispersion and suspension stability of the modified nano-molybdenum disulfide in the base oil system are improved. The improved dispersion state helps the nanosheets form a heat conduction network in the medium, reduces the interfacial thermal resistance, and thus improves the thermal conductivity of the system. The dispersed modified nano-molybdenum disulfide can easily enter the friction contact area with the oil flow, and through physical filling, surface segment isolation, and synergistic participation with other extreme pressure anti-wear agents in the system in the tribochemical reaction, it promotes the formation of the boundary lubricating film, thereby improving the comprehensive thermal conductivity and wear resistance of the lubricating oil system.
[0015] In some embodiments, the bio-based macromolecular hindered phenol is prepared by the following method: Epoxidized soybean oil, hindered phenolic derivatives with terminal hydrogen active groups, and a catalyst are mixed to induce an epoxidative ring-opening addition reaction between the epoxidized soybean oil and the hindered phenolic derivatives with terminal hydrogen active groups, thereby obtaining bio-based macromolecular hindered phenols.
[0016] Further, the hindered phenolic derivative with terminal hydrogen active group includes at least one of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionylhydrazine, and 4-amino-2,6-di-tert-butylphenol. The catalyst includes at least one of tetrabutylammonium bromide, triethylamine, or p-toluenesulfonic acid.
[0017] Through the above embodiments, a catalyst is used to promote the epoxide ring-opening addition reaction between epoxidized soybean oil and hindered phenolic derivatives with terminal hydrogen-containing active groups. The reaction uses epoxidized soybean oil as the backbone, and the hydrogen-containing active groups at the ends of the hindered phenolic derivatives carry out nucleophilic attack on the epoxide bonds, and the hindered phenolic antioxidant active centers are covalently grafted onto the soybean oil backbone, thus constructing a macromolecular structure that combines long-chain aliphatic hydrocarbons, polyester groups and multiple antioxidant active sites. The selected specific hydrogen-terminated hindered phenolic derivatives have suitable reactivity at their end groups, which can complete the ring-opening grafting process relatively gently under the action of selected quaternary ammonium salts, organic bases or organic acids, etc., which helps to reduce side reactions such as self-polymerization of the base oil system and improve grafting efficiency and product structure uniformity. The bio-based macromolecular hindered phenols prepared by the above chemical grafting retain the long-chain aliphatic hydrocarbon and ester group characteristics of soybean oil skeleton, and match the base oil system in terms of polarity and spatial configuration, improving the solubility and dispersion stability of antioxidants in non-polar and weakly polar media. The macromolecular structure formed by covalent grafting increases the relative molecular mass and spatial volume, limiting the thermal migration and volatilization loss of antioxidant molecules under high temperature and thermo-oxidative alternating conditions. The multiple hindered phenol groups integrated on the single molecular skeleton enable it to continuously quench free radicals in the oil phase and friction interface, thereby maintaining the antioxidant life of the lubricating oil system and synergistically protecting the dispersion network of modified nano molybdenum disulfide.
[0018] In some embodiments, the antioxidant includes at least one of antioxidant 168, antioxidant 626, antioxidant 1010, and antioxidant 1076; The defoamer includes at least one of polydimethylsiloxane and polyether-modified polysiloxane; The demulsifier includes at least one of polyoxyethylene-polyoxypropylene block copolymer, polypropylene glycol, and polyethylene glycol monooleate.
[0019] Through the above implementation methods, the selected phosphite-based small molecule antioxidants tend to decompose hydrogen peroxide, while the hindered phenol-based small molecule antioxidants focus on capturing free radicals. With their high migration rate, the small molecule antioxidants respond quickly in the initial or local high oxidation stress areas. Combined with the long-term residence characteristics of bio-based macromolecular hindered phenols, the overall oxidation induction period and thermo-oxidative stability of the high thermal conductivity and wear-resistant lubricating oil are further improved. The selected defoamer has low surface tension, which allows it to spread rapidly at the gas-liquid interface of a high thermal conductivity and wear-resistant lubricating oil system. This helps to change the interfacial tension and accelerate the collapse of air bubbles trapped in the system under high shear agitation conditions of gears or reducers, thereby maintaining the continuity and incompressibility of the physical lubricating oil film in the load-bearing area and ensuring lubrication and heat conduction efficiency. The selected demulsifier has a specific amphiphilic structure and interfacial activity. When faced with water intrusion, it can destroy the stable emulsion layer formed by free water through competitive adsorption at the oil-water interface, promote water droplet coalescence and oil-water separation, thereby reducing the risk of emulsification and deterioration of high thermal conductivity and wear-resistant lubricating oil and maintaining the stability of various physical and chemical properties of the system.
[0020] Secondly, a method for preparing a high thermal conductivity and wear-resistant lubricating oil includes the following preparation steps: Provide the raw materials for the high thermal conductivity and wear-resistant lubricating oil described in the first aspect; The raw materials are mixed to obtain a high thermal conductivity and wear-resistant lubricating oil.
[0021] Thirdly, the application of a high thermal conductivity and wear-resistant lubricating oil according to the first aspect or a high thermal conductivity and wear-resistant lubricating oil prepared according to the method of the second aspect in wind turbine gearboxes and industrial robot reducers.
[0022] Through the above implementation methods, for high stress and alternating loads, modified nano-molybdenum disulfide and sulfurized isobutylene respond sequentially to construct a boundary lubrication film and alleviate adhesive wear; for local heat accumulation, modified nano-molybdenum disulfide relies on steric hindrance to maintain a dispersed state, constructing a heat conduction network, improving thermal conductivity and reducing interface flash temperature; for long-term operation, bio-based macromolecules with hindered phenols rely on structural restriction to reduce volatility, and work synergistically with small molecule antioxidants and the physical barrier of the boundary lubrication film to quench free radicals and delay oxidative degradation; for wide temperature difference, high shear and water intrusion conditions, the base oil system maintains a wide temperature range viscosity, and with the addition of defoamers and demulsifiers, maintains the continuity of the oil film in the load-bearing area and the stability of the system phase.
[0023] Compared with the prior art, the beneficial effects of this application are at least as follows: This application introduces modified nano-molybdenum disulfide with sulfur vacancy defects on its surface and long-chain aliphatic amide segments grafted by Mo-S coordination covalent bonds. By utilizing the steric hindrance effect of the grafted segments, its dispersion and suspension stability in base oil are improved. This dispersion helps to build a heat conduction network and improve the macroscopic thermal conductivity of the system. At the same time, the modified nano-molybdenum disulfide and sulfurized isobutylene form a boundary lubrication film in the friction contact area based on different contact stresses and interface temperature gradients, which improves the overall load-bearing and anti-wear and friction-reducing performance of the system. Bio-based macromolecular hindered phenols were prepared by epoxy ring-opening addition reaction. Their relative molecular mass and spatial volume restrict the thermal migration of molecules, reducing the volatilization loss rate under high-temperature conditions. Their skeletal structure matches the polarity characteristics of the base oil, improving compatibility and solubility uniformity. Under alternating thermo-oxidative conditions, the macromolecular hindered phenols can be retained relatively stably and form a complementary synergy with the rapidly responding small molecule antioxidants in the system, thereby improving the oxidation induction period and thermo-oxidative stability of the high thermal conductivity and wear-resistant lubricating oil. Modified nano-molybdenum disulfide and bio-based macromolecular hindered phenols form a synergistic effect in the system. On the one hand, the physical isolation of the boundary lubrication film weakens the catalytic initiation of the oxidation chain reaction by the metal substrate and reduces the consumption rate of bio-based macromolecular hindered phenols. On the other hand, bio-based macromolecular hindered phenols quench free radicals and reduce acidic byproducts, which not only alleviates metal corrosion and wear, but also protects the grafted fragments on the surface of modified nano-molybdenum disulfide from deep oxidative degradation, thereby maintaining the suspension stability and thermal network integrity of the system under aging conditions. A base oil system was constructed by compounding polyalphaolefins with pentaerythritol fatty acid esters, which takes into account both the ability to maintain viscosity over a wide temperature range and the thermodynamic compatibility of polar additives. Detailed Implementation
[0024] The embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.
[0025] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0026] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0027] In this specification, unless otherwise specified, "parts" refers to "parts by weight".
[0028] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0029] Polyalphaolefin, kinematic viscosity at 100°C is 5.86 mm. 2 / s, kinematic viscosity at 40℃ is 30.9mm. 2 / s, viscosity index is 137, pour point is -65℃, open flash point is 239℃, and Noark volatility mass fraction is 7.0%.
[0030] Pentaerythritol fatty acid ester, specifically pentaerythritol tetraoleate, CAS No.: 19321-40-5; Nano-sized molybdenum disulfide, CAS No. 1317-33-5, plate-like, 2H phase, average particle size 80 nm, aspect ratio 20:1, specific surface area 60 m². 2 / g; Epoxidized soybean oil, epoxy value: 6.2g / 100g, acid value: 0.4mgKOH / g, iodine value: 3.8gI2 / 100g; Polydimethylsiloxane, with a number average molecular weight of approximately 65,000 and a viscosity of 20,000 mmHg. 2 / s; Polyoxyethylene-polyoxypropylene block copolymer, CAS No.: 9003-11-6.
[0031] Preparation Example 1 Preparation of modified nano-molybdenum disulfide: M1: 10 parts of nano-molybdenum disulfide were dispersed in 200 parts of water and subjected to ultrasonic waves (300W power, 30kHz frequency). Then, 1 part of sodium borohydride was added, and the mixture was reacted at 25℃ and 400rpm for 2 hours. The mixture was then filtered, and the filter cake was washed successively with water, ethanol, and dichloromethane to obtain defective nano-molybdenum disulfide. The defective nano-molybdenum disulfide and 2 parts of α-lipoic acid were then dispersed in 190 parts of dichloromethane and reacted at 25℃ and 400rpm for 3 hours, with the addition of ultrasonic waves (300W power, 30kHz frequency). The mixture was then filtered to obtain a filter cake, which was washed twice with 150 parts of anhydrous ethanol and ultrasonic dispersion (300W power, 30kHz frequency). The filter cake was then dried under vacuum at 30℃ to constant weight to obtain carboxylated nano-molybdenum disulfide. M2: Under nitrogen protection and in complete darkness, 9 parts of carboxylated molybdenum disulfide nanoparticles were dispersed in 180 parts of dichloromethane and treated with ultrasound (300W, 30kHz) for 5 minutes. The mixture was then cooled to 0℃, and 1.2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.06 parts of 4-dimethylaminopyridine were added, with the temperature controlled between 0 and 5℃. The mixture was then reacted at 0℃ and 600 rpm for 30 minutes. Oil was then added dropwise. A dichloromethane solution of amine (1.98 parts oleylamine + 10 parts dichloromethane) was heated to 25°C and reacted for 11 h. The mixture was filtered to obtain a filter cake, which was then treated with 200 parts anhydrous ethanol and subjected to ultrasonic treatment (300 W power, 30 kHz frequency) for 8 min. The mixture was then filtered again to obtain another filter cake. The ultrasonic washing with ethanol (300 W power, 30 kHz frequency) was repeated 4 times. The final precipitate was then vacuum dried at 35°C to constant weight to obtain modified nano-molybdenum disulfide.
[0032] Comparative Preparation Example 1-1 Modified nano-molybdenum disulfide: M1': Under nitrogen protection and complete light avoidance, 10 parts of α-lipoic acid were dispersed in 150 parts of dichloromethane; then, 11.1 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.6 parts of 4-dimethylaminopyridine were added at 0℃ and 600 rpm, and the reaction was carried out for 30 min, with the temperature controlled at 0-5℃, to obtain an amidation activation system; then, an oleylamine dichloromethane solution (13.6 parts of oleylamine + 20 parts of anhydrous dichloromethane) was added dropwise, with the temperature controlled at 0-5℃; after the addition was completed, the temperature was naturally raised to 25℃, and the reaction was continued for 12 h under stirring at 400 rpm; after the reaction was completed, the reaction solution was washed once each with saturated sodium bicarbonate solution, water, and saturated brine; the lower organic phase was collected, and anhydrous sodium sulfate was added to dry it to remove water; after filtering to remove anhydrous sodium sulfate, the filtrate was evaporated under reduced pressure at 35℃ to obtain oleylamine-modified α-lipoic acid; M2': Under nitrogen protection and complete light avoidance, 10 parts of nano-molybdenum disulfide and 4.42 parts of oleylamine-modified α-lipoic acid were dispersed in 190 parts of dichloromethane and reacted at 25°C and 400 rpm for 3 h with ultrasonication (300 W power, 30 kHz frequency). The mixture was filtered to obtain a filter cake, which was washed twice with 150 parts of anhydrous ethanol and ultrasonic dispersion (300 W power, 30 kHz frequency). The filter cake was then vacuum dried at 30°C to constant weight to obtain modified nano-molybdenum disulfide.
[0033] Comparative Preparation Examples 1-2 Preparation of modified nano-molybdenum disulfide: M1'': Under nitrogen protection and light-protected conditions, 10 parts of nano-molybdenum disulfide and 2 parts of α-lipoic acid were dispersed in 190 parts of dichloromethane and reacted at 25°C and 400 rpm for 3 h with ultrasonication (300 W power, 30 kHz frequency). The mixture was filtered to obtain a filter cake, which was washed twice with 150 parts of anhydrous ethanol with ultrasonic dispersion (300 W power, 30 kHz frequency). The filter cake was then dried under vacuum at 30°C to constant weight to obtain carboxylated nano-molybdenum disulfide. M2'': Under nitrogen protection and light-protected conditions, 9 parts of carboxylated molybdenum disulfide nanoparticles were dispersed in 180 parts of dichloromethane and treated with ultrasound (300W power, 30kHz frequency) for 5 min; the mixture was then cooled to 0℃, and 1.2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.06 parts of 4-dimethylaminopyridine were added, with the temperature controlled at 0-5℃. The mixture was then reacted at 0℃ and 600rpm for 30 min; then, dropwise addition was made... The oleylamine solution (1.98 parts oleylamine + 10 parts dichloromethane) was heated to 25°C and reacted for 11 h. The mixture was filtered to obtain a filter cake, which was then treated with 200 parts anhydrous ethanol and subjected to ultrasonic treatment (300 W power, 30 kHz frequency) for 8 min. The mixture was then filtered again to obtain another filter cake. The ultrasonic washing with ethanol (300 W power, 30 kHz frequency) was repeated 4 times. The final precipitate was then vacuum dried at 35°C to constant weight to obtain modified nano-molybdenum disulfide.
[0034] Preparation Example 2 Preparation of bio-based hindered macromolecular phenols: Under nitrogen protection and in the dark, 100 parts of epoxidized soybean oil, 2 parts of tetrabutylammonium bromide, and 100 parts of toluene were mixed and stirred at 25°C and 400 rpm for 30 min. The mixture was then heated to 110°C and stirred under reflux for another 30 min. A hindered phenol derivative toluene solution (80 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid + 150 parts of toluene) was then added dropwise over 1.5 h, maintaining the reaction temperature between 110 and 115°C during the addition. The stirring speed was maintained at 400 rpm. The stirring rate was adjusted, and the temperature was maintained at 110℃ for 8 hours of constant temperature reflux reaction. Heating was stopped, and the mixture was allowed to cool naturally to room temperature. The reaction solution was washed once with 50 parts of 5wt% sodium bicarbonate aqueous solution. After standing and separating the layers, the aqueous phase was discarded, and the organic phase was washed with deionized water until the pH of the washing solution was neutral. The organic phase was collected, 15 parts of anhydrous sodium sulfate were added, and the mixture was allowed to stand and dry for 1 hour. The solution was then filtered. The filtrate was distilled under reduced pressure at 80℃ and a gauge pressure of -0.09 MPa to constant weight to obtain bio-based macromolecular hindered phenol.
[0035] Example 1 Preparation of a high thermal conductivity and wear-resistant lubricating oil: S1: Mix 65 parts of polyalphaolefin and 12 parts of pentaerythritol tetraoleate, heat to 70°C, and stir at 400 rpm for 20 min to obtain the base oil system. S2: Add two portions of the modified nano molybdenum disulfide from Preparation Example 1 to the base oil system, stir at 70°C and 5000 rpm for 0.5 h, and then disperse with ultrasonic waves at a frequency of 30 kHz and a power of 300 W to obtain a dispersion system. S3: Add 2 parts of the bio-based macromolecular hindered phenol from Preparation Example 2, 1 part of sulfurized isobutylene, 1 part of antioxidant 168, 0.02 parts of polydimethylsiloxane, and 0.02 parts of polyoxyethylene-polyoxypropylene block copolymer to the dispersion system in sequence; stir at 70℃ and 600 rpm for 1 h; then stir and degas at 70℃, -0.085 MPa, and 150 rpm for 40 min; then filter under pressure through a 3 μm filter while hot; and then let stand and age at room temperature for 24 h to obtain a high thermal conductivity and wear-resistant lubricating oil; the dynamic light scattering test results show that the average particle size of the modified nano molybdenum disulfide in the high thermal conductivity and wear-resistant lubricating oil is 143.8 nm, and the polydispersity index is 0.2273, indicating that the modified nano molybdenum disulfide has achieved stable dispersion in the base oil system, with a narrow particle size distribution and no obvious agglomeration.
[0036] Comparative Example 1 Similar to Example 1, except that in step S2, the modified nano molybdenum disulfide in Example 1 is replaced with nano molybdenum disulfide.
[0037] Comparative Example 2 The preparation is largely the same as in Example 1, except that the modified molybdenum disulfide nanoparticles in Preparation Example 1 are replaced with the modified molybdenum disulfide nanoparticles in Comparative Preparation Example 1-1 in step S2.
[0038] Comparative Example 3 The preparation is largely the same as in Example 1, except that the modified molybdenum disulfide nanoparticles in Preparation Example 1 are replaced with the modified molybdenum disulfide nanoparticles in Comparative Preparation Examples 1-2 in step S2.
[0039] Comparative Example 4 The preparation method is largely the same as in Example 1, except that the bio-based macromolecular hindered phenol in step S3 of Preparation Example 2 is replaced with 1.11 parts of epoxidized soybean oil and 0.89 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid.
[0040] Comparative Example 5 The preparation method is largely the same as in Example 1, except that the bio-based macromolecular hindered phenol in step S3 of Preparation Example 2 is replaced with 1.69 parts of polyalphaolefin and 0.31 parts of pentaerythritol fatty acid ester.
[0041] Comparative Example 6 The preparation method is largely the same as in Example 1, except that the modified nano-molybdenum disulfide in step S2 of Example 1 is replaced with 1.69 parts of polyalphaolefin and 0.31 parts of pentaerythritol fatty acid ester.
[0042] Comparative Example 7 The preparation is largely the same as in Example 1, except that the modified molybdenum disulfide nanoparticles in Preparation Example 1 in step S2 and the bio-based macromolecular hindered phenols in Preparation Example 2 in step S3 are replaced with 3.38 parts of polyalphaolefin and 0.62 parts of pentaerythritol fatty acid ester.
[0043] Test section Wear scar diameter test: The tribological properties of the lubricating oils prepared in the examples and comparative examples were tested according to ASTM D4172-25 standard. Three lower steel balls were placed in an oil box, and test oil was poured into the oil box to a depth of 3 mm above the top of the balls. The upper steel balls were clamped with a fixture. During the test, the three lower steel balls were fixed, while the upper steel ball was rotated by a motor. The spindle speed was 1200 r / min, the test load was 392 N, and the test oil temperature was 75 °C. After the oil temperature reached the set value, it was kept at a constant temperature for 15 min before the test began. The friction time was 60 min. After the test, the three lower test balls were removed, and the wear scar diameter on each steel ball was measured from two mutually perpendicular directions using an optical microscope wear scar analyzer. A total of 6 wear scar diameter values were obtained, and the arithmetic mean of the 6 values was taken as the final wear scar diameter. Each group of samples was tested in parallel at least 3 times, and the average of the 3 tests was taken as the final result.
[0044] Thermal conductivity test: The thermal conductivity of each group of lubricating oils was determined using the transient hot wire method, referring to ASTM D7896-26 standard. After thoroughly mixing the prepared samples, each group was placed in a test cell and allowed to stand in situ at room temperature for 24 hours to ensure that no microbubbles remained in the system and to verify the static dispersion stability of the nanomaterials. Subsequently, the test cell was connected to a constant temperature system, and the test temperature was set to 80℃ without moving the test cell. The temperature was maintained for 45 minutes to eliminate liquid thermal convection caused by heating. After the system reached thermal equilibrium, the measurement was performed. Each group of samples was tested in parallel three times, with a 15-minute interval between each test to ensure that the residual heat around the probe was completely dissipated. The arithmetic mean was taken as the final thermal conductivity record value.
[0045] Antioxidant performance test: The oxidation test of the rotating pressure vessel was conducted according to ASTM D2272-22 standard. 50g of the sample oil from the examples and comparative examples was weighed, along with 5ml of distilled water. A standard electrolytic copper wire coil (3m long, 1.63mm in diameter), polished with 100-grit silicon carbide sandpaper and cleaned and dried with acetone, was placed inside a glass container. The container was placed in an oxygen bomb, and the bomb was first fully purged with high-purity oxygen to remove air. Then, at 25°C, 620kPa of oxygen was finally introduced (standard pressure compensation was performed if the ambient temperature deviated). The device was then placed in a constant-temperature bath at 150°C and rotated at 100rpm around its axis at a 30° angle. The time required from when the device was placed in the constant-temperature bath until the internal pressure stabilized at its highest point and decreased by 175kPa was recorded as the antioxidant induction period of the sample. Each group of samples was tested twice in parallel. The average value of the two results was taken as the final result, provided that the deviation between the two results met the repeatability requirements specified in the standard.
[0046] The test results are shown in Table 1: Table 1
[0047] According to Table 1, Example 1 showed better comprehensive test data compared to Comparative Examples 1-7, indicating that the high thermal conductivity and wear-resistant lubricating oil provided in this application has achieved a good performance balance in terms of thermal conductivity, extreme pressure wear resistance and oxidation life, and verified the synergistic effect of modified nano molybdenum disulfide and bio-based macromolecular hindered phenol based on the friction-oxidation coupling mechanism in the system. The possible reason is that, in Comparative Example 1, the use of unmodified nano-molybdenum disulfide, due to the lack of steric hindrance provided by the surface-grafted long chains, resulted in decreased dispersion stability of nano-molybdenum disulfide in the base oil system, making it prone to agglomeration. This agglomeration not only hinders the formation of a uniform heat conduction network in the liquid medium, leading to a lower macroscopic thermal conductivity, but also causes the agglomerated particles entering the friction contact zone to exhibit wear-like characteristics. This not only interferes with the tribochemical reaction film formation process of isobutylene sulfide on the metal substrate surface, but also increases the risk of inducing local three-body wear, resulting in an increase in the wear scar diameter. Consequently, its anti-wear performance is inferior to that of Comparative Example 6 without added molybdenum disulfide. In Comparative Example 2, modified molybdenum disulfide nanoparticles were prepared using the method of Comparative Preparation Example 1-1. This preparation process employs a strategy of first synthesizing long-chain molecules and then surface bonding. The pre-synthesized oleylamine-modified α-lipoic acid has a large spatial volume, which increases the steric hindrance for the molecule to approach the inorganic nano-interface, hindering its effective bonding and arrangement on the surface of molybdenum disulfide nanoparticles, thus limiting the actual degree of modification of the matrix surface. This structural feature reduces the dispersion and suspension stability of nanoparticles in the base oil medium, thereby limiting the improvement of the thermal conductivity and anti-wear performance of the lubricating oil system to a certain extent. In Comparative Example 3, modified molybdenum disulfide nanoparticles were prepared using the method described in Comparative Preparation Examples 1-2. Since this preparation step did not involve in-situ reduction with sodium borohydride, the probability of exposing coordinated unsaturated sulfur vacancies on the surface of the molybdenum disulfide nanoparticles was relatively low. This made the coordinated fatty acids with active sulfur end groups more likely to bind to the matrix via physical adsorption or weaker interactions, which was not conducive to constructing a stable Mo-S covalent anchor. Under conditions of high shear and thermal stress, the tendency for surface-modified molecules to desorb increased relatively, thus affecting the long-term stability of the modified molybdenum disulfide nanoparticles suspended and dispersed in the medium, which was detrimental to the system's ability to continuously maintain a thermally conductive network and physical isolation effect. In Comparative Example 4, the bio-based macromolecular hindered phenol was replaced with an equal mass of epoxidized soybean oil and a physical mixture of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid. Since the two did not form covalent grafts through ring-opening addition reactions, the small-molecule hindered phenol derivative lacked the structural anchoring effect of the macromolecular skeleton. Under high-temperature thermo-oxidative testing conditions, its tendency to undergo thermal migration and volatilization was relatively increased. This made it difficult for the antioxidant active components to remain stably in the system for a long period of time in order to continuously exert their role in quenching free radicals. In Comparative Example 5, the bio-based macromolecular hindered phenol was removed. Due to the lack of this long-lasting antioxidant component, the system's ability to continuously quench peroxide free radicals under working conditions such as thermal stress was weakened, and the antioxidant induction period was shortened. In addition, the lack of the protective effect of hindered phenol also increased the tendency of the lubricating oil system to undergo deep oxidative degradation to some extent. In Comparative Example 6, modified nano-molybdenum disulfide was removed. The system lacked dispersed nanosheets, hindering the construction of an effective heat conduction network. Furthermore, the absence of the physical filling and interlayer slip-assisted friction-reducing effects of modified nano-molybdenum disulfide in the initial contact phase of micro-protrusions led to a decrease in thermal conductivity and an increase in wear scar diameter. In addition, the lack of a boundary film constructed with nano-molybdenum disulfide to physically isolate the metal surface increased the probability of exposure to the nascent metal interface. This, to some extent, facilitated the catalytic initiation of the oxidation chain reaction on the metal substrate, potentially accelerating the consumption of hindered phenolic macromolecules and reducing the antioxidant induction period of the sample. These results indirectly demonstrate the objective existence of a synergistic friction-oxidation coupling mechanism in the system. In Comparative Example 7, both modified nano-molybdenum disulfide and bio-based macromolecular hindered phenols were removed, leaving only small-molecule extreme pressure anti-wear agents and auxiliary antioxidants in the system. The wear scar diameter and thermal conductivity of this system exhibited the background levels of conventional components. Meanwhile, due to the lack of the sustained effect of hindered phenolic main antioxidants and the synergistic assistance of the nanoparticle physical isolation membrane, the antioxidant induction period of the sample dropped to 94 min. These results collectively indicate that relying solely on conventional small-molecule additive combinations is insufficient to achieve the comprehensive synergistic improvement effect on physicochemical properties that this application aims to construct.
[0048] In addition, the sample from Example 1 was shaken well and placed in an open test container. It was subjected to thermo-coupled aging for 72 hours under constant temperature of 150°C and shear rate of 10,000 rpm using a high-shear dispersion emulsifier. After aging, the sample was cooled to room temperature and allowed to stand for 24 hours to defoam. The stabilized sample was then taken, and the wear scar diameter and thermal conductivity after aging were measured according to the aforementioned method. Each group was tested in parallel for 3 times, and the arithmetic mean was taken as the final recorded value. The wear scar diameter was 0.48 mm and the thermal conductivity was 0.151 W / (m·K), which met the stability requirements.
[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A high thermal conductivity and wear-resistant lubricating oil, characterized in that, The raw materials include the following parts by weight: 65 parts polyalphaolefin, 12-18 parts pentaerythritol fatty acid ester, 1.5-2.5 parts modified nano molybdenum disulfide, 2-5 parts bio-based macromolecular hindered phenol, 1-3 parts sulfurized isobutylene, 1-3 parts antioxidant, 0.01-0.05 parts defoamer, and 0.01-0.05 parts demulsifier; The modified nano-molybdenum disulfide is a nano-molybdenum disulfide whose surface is reduced with sodium borohydride to introduce sulfur vacancy defects and grafted with long-chain aliphatic amide fragments through Mo-S coordination covalent bonds. The bio-based macromolecular hindered phenol is a graft product obtained by an epoxidized soybean oil and a hindered phenol derivative with a terminal hydrogen active group undergoing an epoxidative ring-opening addition reaction; the hindered phenol derivative with a terminal hydrogen active group includes at least one of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionylhydrazide, and 4-amino-2,6-di-tert-butylphenol.
2. The high thermal conductivity and wear-resistant lubricating oil according to claim 1, characterized in that, The modified nano-molybdenum disulfide was prepared through the following steps: M1: Disperse nano-molybdenum disulfide and sodium borohydride in water to remove some sulfur atoms from the surface of nano-molybdenum disulfide to form sulfur vacancies, thereby obtaining defective nano-molybdenum disulfide. Then, disperse the defective nano-molybdenum disulfide and a coordinating fatty acid with active sulfur at the end group in a first organic solvent to form a Mo-S coordination covalent bond with the defective nano-molybdenum disulfide, thereby obtaining carboxylated nano-molybdenum disulfide. M2: The carboxylated nano-molybdenum disulfide, condensing agent, auxiliary condensing agent, and long-chain aliphatic primary amine are dispersed in a second organic solvent, so that the carboxylated nano-molybdenum disulfide reacts with the long-chain aliphatic primary amine to obtain modified nano-molybdenum disulfide.
3. The high thermal conductivity and wear-resistant lubricating oil according to claim 2, characterized in that, The terminated coordinated fatty acids containing active sulfur include at least one of α-lipoic acid and asparagus acid; The long-chain aliphatic primary amine includes at least one of oleylamine and mustyl primary amine; The condensing agent includes N , N' At least one of dicyclohexylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; The auxiliary condensing agent includes at least one of 4-dimethylaminopyridine, 1-hydroxybenzotriazole, and N-hydroxysuccinimide; The first organic solvent includes at least one of dichloromethane, toluene, and 1,4-dioxane; The second organic solvent includes at least one of dichloromethane, toluene, and 1,4-dioxane.
4. The high thermal conductivity and wear-resistant lubricating oil according to claim 2, characterized in that, The modified nano-molybdenum disulfide was prepared through the following steps: M1: Disperse 10 parts of nano-molybdenum disulfide in 150-250 parts of water, add 1 part of sodium borohydride, and react at 20-30°C for 1-3 hours to obtain defective nano-molybdenum disulfide. Then disperse the defective nano-molybdenum disulfide and 1.8-2.2 parts of coordinated fatty acids with active sulfur end groups in 180-240 parts of a first organic solvent, and react at 20-30°C for 3-4 hours to obtain carboxylated nano-molybdenum disulfide. M2: The carboxylated nano-molybdenum disulfide is dispersed in 180-240 parts of a second organic solvent, and then 1.1-1.5 parts of a condensing agent and 0.05-0.15 parts of an auxiliary condensing agent are added. The mixture is reacted at 0-5°C for 0.5-1 h, and then 1.5-2.5 parts of a long-chain aliphatic primary amine are added. The mixture is reacted at 20-30°C for 8-12 h to obtain modified nano-molybdenum disulfide.
5. The high thermal conductivity and wear-resistant lubricating oil according to claim 2, characterized in that, The nano-molybdenum disulfide is in the form of flakes, 2H phase, with an average particle size of 75–125 nm, an aspect ratio of 10–50:1, and a specific surface area of 40–80 m². 2 / g.
6. The high thermal conductivity and wear-resistant lubricating oil according to claim 1, characterized in that, The bio-based macromolecular hindered phenol was prepared by the following method: Epoxidized soybean oil, hindered phenolic derivatives with terminal hydrogen active groups, and a catalyst are mixed to induce an epoxidative ring-opening addition reaction between the epoxidized soybean oil and the hindered phenolic derivatives with terminal hydrogen active groups, thereby obtaining bio-based macromolecular hindered phenols.
7. The high thermal conductivity and wear-resistant lubricating oil according to claim 6, characterized in that, The catalyst includes at least one of tetrabutylammonium bromide, triethylamine, or p-toluenesulfonic acid.
8. The high thermal conductivity and wear-resistant lubricating oil according to claim 1, characterized in that, At least one of the following conditions must be met: 1) The antioxidant includes at least one of antioxidant 168, antioxidant 626, antioxidant 1010, and antioxidant 1076; 2) The defoamer includes at least one of polydimethylsiloxane and polyether-modified polysiloxane; 3) The demulsifier includes at least one of polyoxyethylene-polyoxypropylene block copolymer, polypropylene glycol, and polyethylene glycol monooleate.
9. A method for preparing a high thermal conductivity and wear-resistant lubricating oil, characterized in that, The preparation steps include the following: Provide the raw materials for the high thermal conductivity and wear-resistant lubricating oil according to any one of claims 1 to 8; The raw materials are mixed to obtain a high thermal conductivity and wear-resistant lubricating oil.
10. The application of a high thermal conductivity and wear-resistant lubricating oil according to any one of claims 1 to 8 or a high thermal conductivity and wear-resistant lubricating oil prepared by the method according to claim 9 in wind turbine gearboxes and industrial robot reducers.